Cartan calculi on the quantum superplane - Celik, Salih (AMER INST PHYSICS, 2006)
Cartan calculi on the extended quantum superplane are given. To this end, the noncommutative differential calculus on the extended quantum superplane is extended by introducing inner derivations and Lie derivatives. (c) 2006 American Institute of Physics.
Keywords: COMPACT MATRIX PSEUDOGROUPS; DIFFERENTIAL GEOMETRY; Physics